IMPLEMENTASI PEMBELAJARAN BERBASIS MEDIA KREATIF UNTUK MENINGKATKAN KEMAMPUAN GERAK LOKOMOTOR PADA SISWA KELAS 3 SEKOLAH DASAR - Fatkhul Imron; Widha Srianto (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
The objectives of this pre-experimental study are: (1) to describe the effectiveness of learning by applying creative media on material of basic locomotor movement, (2) to compare the result of basic locomotor movement abilities between students who learn by implementing creative media and by implementing conventional media. This research is a pre-experimental study applying Pretest-Posttest Design. During the research, its subject was given a pre-test and post-test experiment. Conventional learning was provided for the control group, while creative media learning was provided for the experimental group, then data of locomotor movement ability was recorded. The data was analyzed by using SPSS to answer the problem statement. The results of this research are obtained as follows: (1) Learning process of basic locomotor movement by implementing creative media is effective for 3rd grade students of elementary school. (2) Its effectiveness can be referred from the observation results towards learning process of most students considered in good category, completeness learning of the students is greater as many as 19 students or 58%, compared to conventional learning as many as 12 students or 36%. (3) The average test result of the students’ basic locomotor movement ability using creative media is 2.06, while the average ability of students using conventional learning media is 1.86.